Recent Advances toward High‐Efficiency Halide Perovskite Light‐Emitting Diodes: Review and Perspective. Issue 10 (3rd July 2018) - Van Le, Quyet; Jang, Ho Won; Kim, Soo Young
Abstract: Organic–inorganic halide perovskite materials have attracted significant attention during the last few years because of their superior properties for electronic and optoelectronic devices, such as their long charge‐carrier diffusion lengths and high photoluminescence quantum yields of up to 100% with tunable bandgaps over the entire visible spectral range. In addition to solar cells, light‐emitting diodes represent a fascinating application for halide perovskite materials. Here, the recent progress relating to halide perovskite LEDs is reviewed. The current strategies for improving the performance of halide LEDs, focusing on morphological engineering, dimensional engineering, compositional engineering, surface passivation, interfacial engineering, and the plasmonic effect are discussed. The challenges and perspectives for the future development of halide perovskite LEDs are also considered. Abstract : The current progress and strategies toward high‐efficiency halide perovskite light‐emitting diodes (HPLEDs) are summarized. The importance of halide perovskite structures, additives, passivation layers, interlayers, and plasmonic nanoparticles with regard to the performance of devices are discussed. The challenges and perspectives relating to HP materials and HPLEDs are also discussed, offering a guideline for future development of HPLEDs.